2019
DOI: 10.1111/jcmm.14195
|View full text |Cite
|
Sign up to set email alerts
|

The role of intestinal microbiota in cardiovascular disease

Abstract: Accumulating evidence has indicated that intestinal microbiota is involved in the development of various human diseases, including cardiovascular diseases (CVDs). In the recent years, both human and animal experiments have revealed that alterations in the composition and function of intestinal flora, recognized as gut microflora dysbiosis, can accelerate the progression of CVDs. Moreover, intestinal flora metabolizes the diet ingested by the host into a series of metabolites, including trimethylamine N‐oxide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
122
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(127 citation statements)
references
References 101 publications
0
122
0
5
Order By: Relevance
“…Notably, sarcopenia is one of the main conditions involved in the onset of cognitive frailty. Thus, incorporating the Mediterranean diet in the daily habits of patients with cognitive frailty may be a useful strategy for increasing the amount of ω-3 PUFA precursors and, in turn, increasing the availability of anti-inflammatory ω-3 PUFA mediators (e.g., EPA and DHA) (137).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, sarcopenia is one of the main conditions involved in the onset of cognitive frailty. Thus, incorporating the Mediterranean diet in the daily habits of patients with cognitive frailty may be a useful strategy for increasing the amount of ω-3 PUFA precursors and, in turn, increasing the availability of anti-inflammatory ω-3 PUFA mediators (e.g., EPA and DHA) (137).…”
Section: Discussionmentioning
confidence: 99%
“…Non-lethal inhibition of gut bacterial TMA lyases with 3,3-dimethyl-1-butanol prevented atherogenesis in Apoe −/− mice on choline rich diet [10,13]. Furthermore, the microbiome-dependent impact of TMAO on prothrombotic platelet function and arterial thrombosis was demonstrated to be transmissible by fecal transplantation from human donors with low or high TMAO-producing microbiota into GF recipient mice [10,88]. Future clinical studies and experimental research need to address the mechanisms through which TMAO influences CVD and arterial thrombosis.…”
Section: Patterns and Metabolites From The Gut Microbiota As Drivers mentioning
confidence: 95%
“…While choline supplemented diet augmented atherosclerosis and plaque macrophage content in this mouse atherosclerosis study, broad-spectrum antibiotic treatment (0.5 g/L vancomycin, 1 g/L neomycin sulfate, 1 g/L metronidazole, 1 g/L ampicillin) via the drinking water demonstrated that depletion of the microbiota decreased the choline-dependent enhancement of atherosclerotic lesions in male and female Apoe −/− C57BL/6J mice, when kept on a choline-enriched diet at the age of four-weeks until the age of twenty-weeks [16]. Non-lethal inhibition of gut bacterial TMA lyases with 3,3-dimethyl-1-butanol prevented atherogenesis in Apoe −/− mice on choline rich diet [10,13]. Furthermore, the microbiome-dependent impact of TMAO on prothrombotic platelet function and arterial thrombosis was demonstrated to be transmissible by fecal transplantation from human donors with low or high TMAO-producing microbiota into GF recipient mice [10,88].…”
Section: Patterns and Metabolites From The Gut Microbiota As Drivers mentioning
confidence: 99%
See 2 more Smart Citations